Genome-wide identification and characterization of DNA methyltransferases and demethylases in Siraitia grosvenorii - Zang, Yimei; Wang, Chongnan; Su, Jiaxian; Xie, Lei; Mo, Changming; Luo, Zuliang; Ma, Xiaojun (Frontiers in Plant Science, 2025)
DNA methylation and demethylation play a crucial role in plant development, fruit ripening, and the accumulation of secondary metabolites. It is primarily catalyzed and regulated by cytosine-5 DNA methyltransferases (C5-MTases) and DNA demethylases (dMTases). In our study, six C5-MTase and four dMTase genes were identified in Siraitia grosvenorii genome. Phylogenetic analysis demonstrated that the six SgC5-MTase were divided into four categories, SgMET1, SgCMTs, SgDRMs, and SgDNMT2. The four SgdMTase were grouped into SgROS1, SgDML3, SgDME subfamilies. Transcript abundance levels of SgC5-MTase and SgdMTase genes revealed changes during vegetative and reproductive development. Furthermore, the expression of SgdMTase genes was upregulated during fruit ripening, while SgCMT2/3 genes were downregulated. This indicates a potential rise in demethylation, aligning with the accumulation pattern of mogroside V. Our results suggest a role for DNA methylation modifications in the growth, development, maturation, and accumulation of mogrosides, which will also facilitate future epigenetic studies in S. grosvenorii.